Pengaruh Strategi Pemasaran Lembaga Terhadap Kepuasan Pelanggan Jasa Pendidikan di Raudhatul Athfal Darunnajah 2 Cipining Bogor - Rizka Lukmana; M. Mukhlis Nasrulloh; Heri Dermawan; Ahmad Farid (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Marketing strategy is influential in providing satisfaction for service customers, including educational services. With a marketing strategy, it can encourage customer satisfaction for educational services. This research approach uses quantitative methods. The sampling technique in this study used Simple Random Sampling, which was as many as 34 students. The data collection technique is using a questionnaire. The data analysis technique used is simple linear regression. the following results of calculations using Microsoft excel equipped with SPSS 22 show the results of the study that there is an influence between marketing strategy (X) on customer satisfaction of education services (Y) at Raudhatul Athfal Darunnajah 2 Cipining, it is proven that the coefficient of determination of the summary model table value R square = 0.319, to determine the magnitude of the effect of variable x on variable y by 32%. So the results of the coefficient of determination show that 32% of marketing strategies contribute to customer satisfaction in education services, while the rest is 100% - 32% = 68% others are influenced by other factors.